Red cell glyoxalase I and placental soluble aconitase polymorphisms in the three major ethnic groups of Malaysia - Teng, Yao Sheng; Tan, Soon Guan; Ng, Thomas; Lopez, C. G. (Springer-Verlag, 1978)
We surveyed three major ethnic groups in Malaysia for red cell glyoxalase I polymorphism. The allelic frequencies forGLO1 were: Malays, 0.196; Chinese, 0.200; and Indians, 0.287. No rare variant was seen. By means of gel electrophoresis of placenta samples, theACON2s allele was found to be polymorphic in Chinese and Malays. The gene frequencies were 0.045 for Chinese and 0.039 for Malays. Only the commonACONs 1–1 phenotype was present among the 170 Indians we examined.